2010
DOI: 10.1002/cncr.25139
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of lenalidomide plus dexamethasone in relapsed and/or refractory multiple myeloma patients with impaired renal function

Abstract: BACKGROUND:In patients with multiple myeloma, renal impairment (RI) at the time of diagnosis is associated with poor survival. To the authors' knowledge, the current retrospective analysis presented is the first to assess the impact of various degrees of renal dysfunction on safety and efficacy outcomes in a large cohort of patients with relapsed and/or refractory multiple myeloma who received treatment with lenalidomide plus dexamethasone. METHODS: Three hundred fifty-three patients from 2 large phase 3 trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(92 citation statements)
references
References 19 publications
(42 reference statements)
6
85
0
Order By: Relevance
“…Also, more data are needed in for the role of drugs such ixazomib in patients with RF and CrCl < 30 ml/min [21][22][23][24]. For lenalidomide there are several reports indicating a potential role in patients with RF [6,[25][26][27] although the results as primary therapy in patients with severe RF [28] or patients requiring dialysis are not ample [25,29,30]. Pomalidomide may be given without dose modifications in patients with severe RI, but still more data are needed and no data exist in newly diagnosed patients [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Also, more data are needed in for the role of drugs such ixazomib in patients with RF and CrCl < 30 ml/min [21][22][23][24]. For lenalidomide there are several reports indicating a potential role in patients with RF [6,[25][26][27] although the results as primary therapy in patients with severe RF [28] or patients requiring dialysis are not ample [25,29,30]. Pomalidomide may be given without dose modifications in patients with severe RI, but still more data are needed and no data exist in newly diagnosed patients [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The subgroup analyses of data are derived primarily from the Rajkumar study 10 in the first-line setting and from pooled data from the Weber and Dimopoulos studies 1,2,10,18,34,35,39 in the relapsed or refractory setting. These data have been integrated with the clinical expertise of the Hematology dsg to provide support for the recommendations.…”
Section: Key Evidencementioning
confidence: 99%
“…The recommendation for use in mild-to-moderate renal dysfunction (creatinine clearance ≥30 mL/min and ≤60 mL/min) is based on a subgroup analysis of pooled data from the pivotal relapsed or refractory studies 1,2 reported by Dimopoulos et al 18 Given the small sample of patients with severe renal failure (creatinine clearance <30 mL/min) enrolled in the studies, the Hematology dsg cannot make recommendations for that population.…”
Section: Key Evidencementioning
confidence: 99%
“…8 Improvement in renal function has also been reported in up to 72% of patients with RRMM with lenalidomide plus dexamethasone treatment. 8,9 However, little is known about the efficacy and tolerability of newer therapies in patients with NDMM with RI because many phase 3 clinical trials exclude patients with moderate to severe RI. [10][11][12] The Frontline Investigation of Revlimid and Dexamethasone vs. Standard Thalidomide (FIRST) study is a phase 3, international, randomized, open-label trial of lenalidomide plus low-dose dexamethasone (Rd) in patients with NDMM who are ineligible for stem cell transplant (SCT).…”
Section: Introductionmentioning
confidence: 99%
“…9 However, in these studies, standard lenalidomide dosing was associated with increased toxicity and more frequent use of subsequent dose reductions and interruptions due to AEs in patients with moderate to severe RI vs. patients with mild or no RI. 9 Recommendations have since been made for lenalidomide starting dose adjustments for moderate to severe RI based on pharmacokinetic data. 7,17 Lenalidomide is not nephrotoxic, 18 but is primarily renally excreted, 7 such that RI greatly affects its pharmacokinetics.…”
mentioning
confidence: 99%